- Impementasi Teknologi Asistif dalam Pembelajaran Bagi Siswa Berkebutuhan Khusus: - - Amelia Rizky Idhartono; Hidayati, Nurul; Sambira Mambela; Margareta Vernanda Moi; Aisyah Safarina Subekti (Kanigara, 2024)
Every children of Indonesia have the same right to get a good educational quality in their life, including special needs children (ABK) with all the speciality and different characteristics they have. The held of special education had been a responsibility to be done and must be supported with good fasilities. It’s not a new thing if special needs teacher having difficulties in teaching his/heir students. That’s why it’s needed precise and careful decision from the teacher in doing teaching materials, strategy, methods, and teaching tools for special needs children, to be impelemnted in learning processes. Educational media as atools in delivering teaching materials has been one of the factors that could support the raising of the learning results. In digital transformation eras, assistive technology as learning media for special needs children is badly needed. The using of assistive technology that match the needs of special needs children can uprise the effectivity of the learning activities held by students inside and outside the class. Teachers were not only have the responsibility to make decision and implement assistive technology that match the learning needs. to each speciality, but they needed to develop the ideas and creativity to create and or modificate assistive technology independently. The expertise to own strategy and methods in using assistive technology must had by teachers so they could impelement them to their special needs children correctly. Besides, it needs an evaluation to the success of the use of assistive technology in the learning processes, so the could doing the right things if they were certain problems. The partner of this community service program (PkM) were the 50 teachers of SLB Dharma Wanita Sidoarjo. The aims of the training and monitoring held in the theme of “ The Implementation of Assistive Technology in The Learning of Special Needs Students” were to support the teacher to have the ability to decide and implement assistive technology that suite the learning needs. The community service program were held online at November 18th 2023 from 2 PM until 5 PM. At the program, beside the lecturer, there also the students of Pkh University PGRI Adi Buana were involved.